Evaluation of Some Biochemical Factors Associated with Rheumatoid Arthritis - Ibrahim, Tabarak Siraj; hasan, bushra (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Rheumatoid arthritis (RA) is a systemic disease that causes chronic inflammation, primarily affecting the synovial joints in the hands and feet. Laboratory investigations, such as  C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), lipid profile, and matrix metalloproteinase-1 (MMP-1), evaluate the body's inflammation level. Rheumatoid arthritis is generally progressive, causing fatigue and weakening of the muscle joints. Despite recent treatment improvements, there is no known cure for RA. The study aimed to find the role of chemokine MMP-1 as a biomarker in serum samples of 80 patients with RA and 40 healthy subjects. The mean of MMP-1 was significantly higher in patients with RA compared to the control group (MMP-1: 3.27 ± 0.10 ng/mL vs. 1.40 ± 0.11 ng/mL, respectively). The results demonstrated a statistically significant distinction between the two groups. The binary logistic regression analysis revealed that MMP-1 had a statistically significant association with the occurrence of RA. Additionally, it was shown that MMP-1 had an area under the curve of 0.939 in people diagnosed with RA. Both of these experiments provided evidence of this result. According to the findings of the study, there is a possibility that MMP-1 has a role in the pathogenesis of RA since it was shown that patients with RA had higher levels of serum MMP-1, CRP, ESR, and lipid profile when compared to the control group. In conclusion, serum MMP-1 serves as a reliable diagnostic marker, accurately distinguishing individuals with active RA from control subjects.